Psychological Burden and Psycho-Oncological Interventions for Patients With Hepatobiliary Cancers–A Systematic Review - Graf, Johanna; Stengel, Andreas (Frontiers in Psychology, 2021)
Background Worldwide, hepatobiliary cancers are frequent diseases and often accompanied by a poor prognosis. These cancers, with hepatocellular carcinoma (HCC) and cholangiocarcinoma (CHC) being the most frequent, are often associated with a considerable amount of psychological burden such as anxiety, depressiveness and reduced health-related quality of life which may lead to psychiatric comorbidities. This systematic review gives an overview on psychological burden and on the effectiveness of psycho-oncological interventions for patients with HCC and CHC. Methods The databases PubMed, PubPsych and PsycINFO were used and searched using the following combination of terms: (Neoplasm OR Cancer OR Tumor OR Carcinoma) AND (Psycho-Oncology OR Psychotherapy OR Psychiatr*) AND (Liver OR Hepatic OR Hepatocellular OR Gallbladder OR Bile*). Studies were eligible for inclusion if investigating patients affected with tumors of the liver (HCC/CHC) and using diagnostic instruments to assess mental health symptoms and research concerning specific psycho-oncological interventions. In total, 1027 studies were screened by one author with regard to title and abstracts. Afterwards, the two authors of the paper discussed inclusion of possible articles. Results Twelve studies focusing on distress, anxiety and depression symptoms as well as quality of life among patients with HCC/CHC and three studies on psycho-oncological interventions were included. Patients suffering from hepatobiliary cancers often experience considerable psychological burden. A quarter of patients suffer from depressive symptoms; anxiety is even more common among these patients with almost 40%. The health-related quality of life of those affected is reduced in almost all areas, suicide rates increased and the level of distress is considerably increased in one third of patients even in comparison to those with other kinds of cancer. By psycho-oncological intervention the prevalence of depressive symptoms and anxiety can be reduced, while the quality of life and also the survival rate of patients with hepatobiliary cancer can be increased. Discussion & Conclusion Psychological burden is high in patients with hepatobiliary cancers as reflected in high levels of depressiveness and anxiety as well as reduced quality of life. The use of psycho-oncological interventions can reduce psychological burden and increase quality of life compared to patients receiving standard support only.